Automatic Software Adaptation After Reconfiguring an Autonomous Manufacturing Systems. (2014) - Telgen, Daniël; Moergestel, Leo van; Puik, Erik; Brink, Laurens van den; Bakker, Tommas; Hustinx, Alexander; Meyer, John-Jules
No abstract available